Acute, chronic, and genotoxic studies on the protopine total alkaloids of the Macleaya cordata (willd.) R. Br. in rodents - Dong, Zhen; Tang, Shu-sheng; Ma, Xiao-lan; Tan, Bin; Tang, Zhao-shan; Li, Chang-hong; Yang, Zi-hui; Zeng, Jian-guo (Frontiers in Pharmacology, 2022)
The protopine alkaloids are widely distributed within the opium poppy family and have a wide range of pharmacological effects. MPTA is a product of the protopine total alkaloids extracted from the Macleaya cordata (Willd.) R. Br.. Previously, we reported good anti-inflammatory activity of MPTA as well as oral acute and sub-chronic toxicity studies in rats. In order to perform a systematic toxicological safety assessment of MPTA, oral acute toxicity, genotoxicity (bone marrow cell chromosome aberration test, sperm abnormality test, bone marrow cell micronucleus test, and rat teratogenicity test), and chronic toxicity in mice were performed in this study. In the oral acute toxicity test, the LD50 in ICR mice was 481.99 mg/kg, with 95% confidence limits ranging from 404.27 to 574.70 mg/kg. All three mutagenicity tests tested negative in the range of 60.25 to 241.00 mg/kg. The results of the teratogenicity test in rats showed no reproductive or embryonic developmental toxicity at only 7.53 mg/kg, which can be considered as a no observed effect level (NOEL) for the teratogenicity test. Therefore, MPTA is safe for use at the doses tested, but attention should be paid to the potential risk to pregnant animals and the safety evaluation and toxicity mechanisms in target animals should be further investigated.